2021
DOI: 10.3389/fnhum.2021.640574
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Bases of Comorbidity in Migraine

Abstract: Despite that it is commonly accepted that migraine is a disorder of the nervous system with a prominent genetic basis, it is comorbid with a plethora of medical conditions. Several studies have found bidirectional comorbidity between migraine and different disorders including neurological, psychiatric, cardio- and cerebrovascular, gastrointestinal, metaboloendocrine, and immunological conditions. Each of these has its own genetic load and shares some common characteristics with migraine. The bidirectional mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 517 publications
(175 reference statements)
4
58
0
2
Order By: Relevance
“…Although it is a matter of speculation, we may categorize MOH into three types: young people who have just started working and experienced severe stress specific to the young workers [ 32 ], middle-aged people who are busy with both work and child-rearing, and the older probably with mild cognitive disorder or anxiety who uses frequent analgesic. The older also tend to have common comorbidities like other pain syndromes, sleep-related disorders, and gastrointestinal disorders, which aggravate migraine, supposedly leading to MOH development [ 33 ]. Given the social background where developing MOH, classification based on age and frequency of medication may be an important perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is a matter of speculation, we may categorize MOH into three types: young people who have just started working and experienced severe stress specific to the young workers [ 32 ], middle-aged people who are busy with both work and child-rearing, and the older probably with mild cognitive disorder or anxiety who uses frequent analgesic. The older also tend to have common comorbidities like other pain syndromes, sleep-related disorders, and gastrointestinal disorders, which aggravate migraine, supposedly leading to MOH development [ 33 ]. Given the social background where developing MOH, classification based on age and frequency of medication may be an important perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our findings are consistent with previously identified migraine-relevant lipid mediators associated with headache pain mechanisms and associated neuroinflammatory changes, and underscore the potential that peripheral plasma lipid mediator changes can give insights to central migraine mechanisms, in particular in the context of the aura phase and hemiplegic migraine. Given the overlap in their pathophysiology, the observed changes in peripheral body fluids may be of relevance also for other central nervous system disorders that are comorbid with migraine, such as epilepsy and stroke [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine was associated with Helicobacter pylori infection in several studies (reviewed in [ 1 , 2 ]). A meta-analysis including five case–control studies showed a higher H. pylori infection in migraineurs than controls (33%) [ 140 ].…”
Section: Migraine and Functional Gi Disordersmentioning
confidence: 99%
“…Functional disorders of the gastrointestinal (GI) tract are frequently associated with neurological diseases, including migraine, and are a serious diagnostic problem due to nonspecific syndromes (reviewed in [ 1 , 2 ]). Migraine is bidirectionally comorbid with several other disorders, including neurological, psychiatric, cardio- and cerebrovascular, GI, metaboloendocrine, and immunological diseases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation